The changing nature of customary international law : methods of interpreting the concept of custom in international criminal tribunals - Arajarvi, Noora (London : Routledge, 2014)
'This book examines the evolution of customary international law (CIL) as a source of international law analyzing the substantive definitions of state practice and opinio juris, the methods of their discovery and their increasing interlinked nature. It focuses on the importance of CIL in the development of international criminal law and in particular the ways in which international criminal courts and'hybrid' criminal tribunals can be said to be changing the ways in which CIL is determined. The book examines the role of international courts and tribunals in changing the nature of custom, analyzing the methodologies employed by the International Criminal Tribunal for Former Yugoslavia, the International Criminal Tribunal for Rwanda, Special Tribunal for Lebanon, the Extraordinary Chambers in the Courts of Cambodia, and the International Criminal Court. Through examination of the case-law and the reasoning of the courts Noora Arajarvi demonstrates that the tribunals have on occasions tilted towards innovative approaches in their interpretation and methods of finding the applicable customary international law. She shows how and to what extent the court's chosen method of application of CIL affects the process of custom formation as the judges may have the function of both applying and forming rules of CIL. This raises the question as to what level of judicial activism that should be acceptable in international courts as regards CIL'--
'This book examines the evolution of customary international law (CIL) as a source of international law. Using the International Criminal Tribunal for the Former Yugoslavia (ICTY) as a key case study, the book explores the importance of CIL in the development of international criminal law and focuses on the ways in which international criminal courts and'hybrid' criminal tribunals can be said to change the ways in which CIL is determined. In doing so, the book surveys the process and substance of CIL, as well as the problematic distinction between the elements of state practice and opinio juris. By applying a positivist approach, Noora Araji analyses the methodologies employed by the ICTY, International Criminal Tribunal for Rwanda, Special Tribunal for Lebanon, the Extraordinary Chambers in the Courts of Cambodia, and the International Criminal Court. Through examination of the case-law and the reasoning of the courts, Arajarvi demonstrates to what extent the court's chosen method of application of CIL affects the process of custom formation. The book will be of great value to researchers and scholars of international law, international relations, and practitioners with interests in customary international law'--
Introduction -- Genesis of customary international law and international criminal law -- New concept of customary international law : the role of the international criminal judge -- Customary international law in the decisions of the ICTY [International Criminal Tribunal for the Former Yugoslavia] -- The principle of legality and customary international law -- The need for a new conceptual framework for the sources in international law -- General conclusion.
Includes bibliographical references (pages 166-181) and index.
Keywords: Customary law, International; International criminal courts